Can we reconstruct the textual history of the Hebrew Bible?. Issue 11 (27th December 2017) - Pakkala, Juha
Abstract: Variant readings in manuscripts and other documented evidence show that the Hebrew Bible was the focus of intensive scribal activity in its early transmission. Text criticism, which evaluates variant readings, is recognized as an important method, but biblical scholarship uses its results only haphazardly. Historical criticism, which can be divided into literary and redaction criticism, reconstructs the history based on inconsistencies in the text itself. Although dominant especially in continental Europe until the 1980s, historical criticism never received universal recognition, and its influence has diminished in recent decades. This paper presents the rationale of historical criticism and discusses recent challenges to it.